Evidence on Policies to Increase the Development Impacts of International Migration - David McKenzie; Dean Yang (Institute for the Study of Labor (IZA), 2014)
International migration offers individuals and their families the potential to experience immediate and large gains in their incomes, and offers a large number of other positive benefits to the sending communities and countries. However, there are also concerns about potential costs of migration, including concerns about trafficking and human rights, a desire for remittances to be used more effectively, and concerns about externalities from skilled workers being lost. As a result there is increasing interest in policies which can enhance the development benefits of international migration and mitigate these potential costs. We provide a critical review of recent research on the effectiveness of these policies at three stages of the migration process: pre-departure, during migration, and directed towards possible return. The existing evidence base suggests some areas of policy success: bilateral migration agreements for countries whose workers have few other migration options, developing new savings and remittance products that allow migrants more control over how their money is used, and some efforts to provide financial education to migrants and their families. Suggestive evidence together with theory offers support for a number of other policies, such as lowering the cost of remittances, reducing passport costs, offering dual citizenship, and removing exit barriers to migration. Research offers reasons to be cautious about some policies such as enforcing strong rights for migrants like high minimum wages. Nevertheless, we find the evidence base to be weak for many policies, with no reliable research on the impact of most return migration programs, nor for whether countries should be trying to induce communal remitting through matching funds.
Keywords: O15; F22; 330; migration policy; remittances; return migration; impact evaluation